2011
DOI: 10.1523/jneurosci.3102-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

μ-Opioid Receptor Activation in the Basolateral Amygdala Mediates the Learning of Increases But Not Decreases in the Incentive Value of a Food Reward

Abstract: The decision to perform, or not perform, actions known to lead to a rewarding outcome is strongly influenced by the current incentive value of the reward. Incentive value is largely determined by the affective experience derived during previous consumption of the reward-the process of incentive learning. We trained rats on a two-lever, seeking-taking chain paradigm for sucrose reward, in which responding on the initial seeking lever of the chain was demonstrably controlled by the incentive value of the reward.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 43 publications
(83 reference statements)
3
67
0
Order By: Relevance
“…Previous studies demonstrate that opioids acting at MORs appear to imbue food with a hedonic quality that promotes feeding (Doyle et al, 1993;Giraudo et al, 1999). In addition, recent studies suggest that endogenous opioids, such as enkephalin, can impact the motivational properties of food (Hayward et al, 2006;Mahler and Berridge, 2009;Wassum et al, 2011). Overall, our study provides support for these findings using a novel licking microstructure approach, and elucidates a complex involvement of endogenous opioids in feeding and body weight control.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Previous studies demonstrate that opioids acting at MORs appear to imbue food with a hedonic quality that promotes feeding (Doyle et al, 1993;Giraudo et al, 1999). In addition, recent studies suggest that endogenous opioids, such as enkephalin, can impact the motivational properties of food (Hayward et al, 2006;Mahler and Berridge, 2009;Wassum et al, 2011). Overall, our study provides support for these findings using a novel licking microstructure approach, and elucidates a complex involvement of endogenous opioids in feeding and body weight control.…”
Section: Discussionsupporting
confidence: 79%
“…Recent studies suggest that endogenous opioids may not only mediate the hedonic properties of food, but also its motivational properties (Hayward et al, 2006;Mahler and Berridge, 2009;Wassum et al, 2011). Again, the largely pharmacological methods employed to date are unable to shed light on the identity of the endogenous opioids involved.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we previously reported that naloxone-induced blockade of opioid receptors in the nucleus accumbens shell or core during changes in experienced value attenuated the performance of consummatory taste reactivity reflexes but had no effect on the value of the instrumental outcome. In contrast, naloxone infused into the basolateral amygdala did not alter taste reactivity reflexes but completely blocked changes in reward value (Wassum et al, 2009(Wassum et al, , 2011). …”
Section: The Role Of the Accumbens In Incentive Motivationmentioning
confidence: 87%
“…Only if the reward (e.g., a particular food) is consumed in a new shifted physiological state (e.g., hunger), and the individual experiences the increased pleasantness of consuming the reward in the shifted physiological state (e.g., eating that particular food when hungry), is the expected pleasantness consequently modified (Balleine, 1992(Balleine, , 2005Dickinson and Balleine, 1994). Studies showed that if the encoding of the increased valence of the reward under a shifted physiological state is pharmacologically blocked, individuals do not adapt the effort they mobilize to obtain the food reward according to the new physiological state (Wassum et al, 2011a). Motivational behaviors driven by expected pleasantness thus depend upon the episodic memories of prior experiences with the rewards.…”
Section: Differentiating Expected Pleasantness From Affective Relevanmentioning
confidence: 99%